Factors that influence women aspire to work: A case study of female staff at UiTM Malacca / Raja Ratifah Raja Mat and Nur Nadia Arshad - Raja Mat, Raja Ratifah; Arshad, Nur Nadia (Faculty of Administrative Science and Policy Studies, 2013)
In this study, the researchers focus on the factors influencing aspire to work at UiTM Malacca. The purpose of the study is to examine the relationships between independent variables toward dependent variable. Besides, the researchers also want to examine which independent variables have high significant relationship with the dependent variables. For this study, the researchers use the simple random technique. The total population was 130 respondents and the selected respondents was 98 in UiTM Malacca. Based on Morgan and Krejcie table, the proposed respondents are 97 respondents. The study conducted had used several methods such as reliabilibity test, normality test and the pearson correlation. The finding shows that the most significant factor in influencing women to work is economic condition followed by level of education and family background. Based on the research findings, all the factors have a positive relationship and can influence women aspire to work at UiTM Malacca.